Implementation of Islamic Religious Education Learning Long Distance During the Covid-19 Pandemic - Widiyawati (DIROSAT: Journal of Education, Social Sciences & Humanities, 2023)
Islamic Religious Education is a business in the form of teaching, guiding and caring for students so that later after completing their education they are able to understand, live and apply the Islamic religion, and make it a way of life both individually and in society. In the midst of the Covid-19 pandemic, the teaching and learning process is carried out at home or distance education, although the learning process must still be carried out according to existing regulatory policies, in this case there is a need for new applications, especially in Islamic religious education lessons, because it will affect its implementation. This research was made to find out the implementation of distance learning and obstacles in distance learning in the midst of the Covid-19 pandemic in learning Islamic religious education in class X SMK Negeri 2 Indramayu. This research was conducted using a qualitative method with case studies at SMK Negeri 2 Indramayu. . The data collection techniques used by researchers are interviews, observation and documentation. However, because of the pandemic that is currently sweeping the world, researchers have focused more on research by using interviews with primary data sources, namely classroom teachers and special companion teachers and with secondary data sources, namely school principals. The conclusions from this study are that first the Implementation of Distance Learning in Islamic Religious Education Learning in the midst of the Covid-19 Pandemic is implemented using an online system and using Web Learning media http://smkn2indramayu.sch.id/ele itself from schools to make it easier for students to overcome learning difficulties in the midst of this pandemic and aim to break the chain of the spread of Covid-19 in Indonesia. The inhibiting factor is a problem that is handled well, such as students not having cellphones and parents' economic factors which are difficult and can damage their health if they use them for too long. Supporting factors are system reinforcement that helps the continuity of distance learning to be carried out because it is more effective, efficient in terms of cost and time usage.